Modeling plankton diversity in a coupled optical-biogeochemical ocean framework - Álvarez, Eva; Occhipinti, Guido; Cossarini, Gianpiero; Solidoro, Cosimo; Lazzari, Paolo (Frontiers in Ecology and Evolution, 2025)
Biodiversity is crucial to the role of the plankton in marine food webs and biogeochemical cycles. Plankton community modelling is a critical tool for understanding the processes that shape marine ecosystems and their impacts on global biogeochemical cycles. But incorporating the fine-scale diversity of plankton is challenging because it makes the models more uncertain and could affect their accuracy in simulating energy and matter fluxes. Currently, state of the art models do not include plankton diversity explicitly and pool taxa with similar traits into a limited number of state variables or functional types. The aim of this work is to increase the realism of the representation of plankton biodiversity in the community Biogeochemical Flux Model (BFM) that resolves spectrally light transmission in the water column, while keeping the simulated biogeochemistry and optical properties consistent with observations. The objective is to have an optical-biogeochemical ecosystem model designed for understanding the emergent patterns of global plankton distributions. We present the model in a one-dimensional water column configuration that allows for the rapid comparison of model runs with local observations. We show that introducing this community complex representation enable to explore the underlying dynamics of plankton types present in the community while the biogeochemical and optical indicators simulated by the model remain comparable to observations. This diversity-capable BFM provides an integrated framework suitable for exploring the links between plankton community structure and ecosystem functioning, deciphering the potential impacts of changes in diversity on ocean color, to ultimately simulate biodiversity in the forthcoming decades under climatic projections.